Acute promyelocytic leukemia co-existing with JAK2 V617F positive myeloproliferative neoplasm: a case report - Mamorska-Dyga, Aleksandra (Stem Cell Investig, 2016)
The V617F mutation of Janus-associated kinase 2 (JAK2) is commonly seen in myeloproliferative neoplasms (MPN). Transformation of JAK2 positive MPNs to acute leukemia has been reported. We here report a case of acute promyelocytic leukemia which was later confirmed to have a co-existing JAK2 V617F positive MPN. In addition, the patient was found to have FLT3-TKD mutation, which, together with PML/RARa, could play a role in the MPN transformation to APL.